ANALYSIS OF THE INFLUENCE OF PSYCHOLOGICAL, SOCIODEMOGRAPHIC, AND FINANCIAL LITERACY FACTORS ON CHILDREN EDUCATION FUND PLANNING FOR INDONESIAN MILLENIAL PARENTS - Agnes Renata Rajagukguk; Khaira Amalia Fachrudin; Amlys Syahputra Silalahi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Education is very important for children's future. It is the basic capital for preparing human quality. That is why setting up a children's education fund is one of the most important tasks for parents. However, this is a challenge for millennial parents because of the high cost of education in Indonesia. The purpose of this study is to analyze psychological and sociodemographic factors related to planning children's education funds. This study examined 415 Indonesian millennial parents who were selected by accidental sampling technique and tested using the PLS SEM statistical analysis method. This study uses a 95% confidence level, ???? = 5%. The results of the research on psychological factors namely future time perspective and financial risk tolerance have a positive and significant effect on children education funds planning. Sociodemographic factors namely education has a negative and significant effect on children education funds planning. While sociodemographic factors namely income has a positive but not significant effect on children education funds planning. Future time perspective has a positive and significant impact on financial literacy. Education has a negative and insignificant effect on financial literacy, while income has a positive and not significant effect. Financial literacy has succeeded in mediating the effect of future time perspective on children education funds planning, while financial literacy has not succeeded in mediating the effect of education and income on children education funds planning. While sociodemographic factors namely income has a positive but not significant effect on children education funds planning. Future time perspective has a positive and significant impact on financial literacy. Financial literacy has succeeded in mediating the effect of future time perspective on children education financial planning, while financial literacy has not succeeded in mediating the effect of education and income on children's education financial planning. while income has a positive and not significant effect. Financial literacy has succeeded in mediating the effect of future time perspective on children education funds planning, while financial literacy has not succeeded in mediating the effect of education and income on children education financial planning.